Combining Artificial Intelligence with Augmented Reality and Virtual Reality in Education: Current Trends and Future Perspectives - Georgios Lampropoulos (Multimodal Technologies and Interaction)
The combination of artificial intelligence with extended reality technologies can significantly impact the educational domain. This study aims to present an overview regarding the combination of artificial intelligence with augmented reality and virtual reality technologies and their integration in education through an analysis of the existing literature. Hence, this study examines 201 documents from Scopus and the Web of Science (WoS). This study focuses on examining the basic characteristics of the document collection, highlighting the most prevalent themes, areas, and topics, exploring the thematic evolution of the topic, revealing current challenges and limitations and on identifying emerging topics and future research directions. Based on the outcomes, a significant annual growth rate (60.58%) was observed indicating the increasing interest in the topic. Additionally, the potential of combining artificial intelligence with virtual reality and augmented reality technologies to provide personalized, affective, interactive, and immersive learning experiences across educational levels in both formal and informal settings supporting both teachers and students arose. Therefore, through this combination, intelligent tutoring systems (ITSs), which offer behavioral, cognitive, and social personalization, have a virtual presence, and can effectively be used as tutors or peer learners, can be created. Such ITSs can be characterized as affective and social entities that can increase students’ learning performance, learning motivation, and engagement and promote both self-directed learning and collaborative learning. This study also highlights the need to examine how the physical presence that characterizes some new technologies compares to the virtual presence that extended reality technologies offer in terms of overall learning outcomes and students’ development.